KINEMATICS OF SPERMATOZOA IN FRESH AND FROZEN SEMEN OF PESISIR CATTLE - Ramadhan, Rio; Ananda; Hendri (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2025)
This study aimed to evaluate the quality and kinematics of spermatozoa in fresh and frozen semen of coastal cattle. Semen of coastal cattle was collected using an artificial vagina from 2 males, fresh semen was tested and frozen using tris egg yolk diluent. Fresh and frozen semen of coastal cattle were evaluated using a Computer Assisted Sperm Analyzer (CASA). This study used a t-test analysis by comparing the quality and kinematics of spermatozoa of fresh semen and frozen semen of coastal cattle. The parameters observed were macroscopic, microscopic and CASA quality observations. The results showed the kinematics of fresh and frozen semen motility (83.83%; 71.68%) and the kinematics of progressive motility of fresh and frozen semen (80.81%; 59.56%). Based on the results of the t-test analysis, it was found that t count > t table, the kinematics of fresh semen spermatozoa had a significant effect on the frozen semen of Pesisir cattle on the motility of fresh semen and frozen semen, on the progressive motility of fresh semen and frozen semen. The characteristic values ​​of kinematics in fresh semen and frozen semen of Pesisir cattle were respectively velocity curvilinear (VCL) 178.94 μm/s and 108.52 μm/s; velocity straight line (VSL) 96.61 μm/s and 49.34 μm/s; velocity average path (VAP) 114.99 μm/s and 64.04 μm/s; linearity (LIN) 0.53% and 0.44%; straightness (STR) 0.83% and 0.75%; wobble (WOB) 0.64% and 0.58%; lateral head displacement (ALH) amplitude 5.83 μm and 5.15 μm; beat cross frequency (BCF) 35.28 Hz and 24.65 Hz. The kinematics of fresh and frozen semen spermatozoa significantly affect the value of motility characteristics. The conclusion of the results of this study is that there is a decrease in the quality of fresh semen kinematics and frozen semen kinematics spermatozoa on the value of motility characteristics, namely on the speed of spermatozoa at the velocity curvilinear (VCL), velocity straight line (VSL), and velocity average path (VAP), linearity (LIN), straightness (STR), and wobble (WOB) and on the distance value of spermatozoa amplitude lateral head displacement (ALH) and beat cross frequency (BCF).